1984
DOI: 10.1099/00222615-18-3-355
|View full text |Cite
|
Sign up to set email alerts
|

The Bactericidal Action of Human Serum on Bacteroides Species

Abstract: SUMMARY. Sera obtained from 60 healthy normal subjects were tested for their inhibitory action against four clinical isolates of the Bacteroides fragilis group. All the sera inhibited clinical strains of B. vulgatus and B. ovatus, 92% of 60 sera inhibited B. thetaiotaomicron and 62% inhibited B. fragilis. Bacterial inhibition required components of uninactivated serum and was related to the serum concentrations and species of the bacteria. The viable counts of all the strains, except B. fragilis, were signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

1987
1987
2004
2004

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…The capsular polysaccharide B. fragilis acts as a protector against neutrophil phagocytes and the complement bactericidal activity; it can produce abscesses in animals (Lindberg & Weintraub 1985). Moreover, all the tested strains showed characteristics such as β-hemolytic, hydrophilic, and human or horse serum resistant, in accordance with Rotimi and Eke (1984), Oyston and Handley (1990), and Namavar et al (1991).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The capsular polysaccharide B. fragilis acts as a protector against neutrophil phagocytes and the complement bactericidal activity; it can produce abscesses in animals (Lindberg & Weintraub 1985). Moreover, all the tested strains showed characteristics such as β-hemolytic, hydrophilic, and human or horse serum resistant, in accordance with Rotimi and Eke (1984), Oyston and Handley (1990), and Namavar et al (1991).…”
Section: Discussionmentioning
confidence: 65%
“…The serum bactericidal activity is perhaps the most important host's resistance factor against the systemic bacterial invasion. Thus, the resistance of the B. fragilis strain against human or horse sera may explain its pathogenic potential in severe clinical infections (Rotimi & Eke 1984). Namavar et al (1991) showed that avirulent B. fagilis strains were more sensitive to serum than the virulent ones, indicating that the complement is crucial for killing of avirulent strains.…”
Section: Discussionmentioning
confidence: 99%
“…A resistência ao soro representa também alguma associação com a cápsula e/ou com a camada lipopolissacarídica, participando em conjunto da virulência desse grupo microbiano. É sabido que a atividade do soro constitui um importante fator de resistência do hospedeiro contra a invasão sistêmica pelos microrganismos EKE, 1984). Da mesma forma, a maioria dos isolados mostraram resistência à 60 o C por 30 minutos e em alguns casos, por mais de 60 minutos, o que sem dúvida também colabora com o potencial patogênico dessas bactérias (SHARP, 1999).…”
Section: Discussionunclassified